New species and taxonomic notes of Agraeciini from Mount Malindang (Philippines: Mindanao) (Tettigoniidae: Conocephalinae: Agraeciini) - Rivera, Rodrin R.; Daguplo, Jiandy; Mondejar, Eddie P.; Nuñeza, Olga Macas; Tan, Ming Kai (Zootaxa, 2025)
From Mount Malindang Range Natural Park in Misamis Occidental, Mindanao in the Philippines, two new species of Agraeciini are described: Anthracites sineaureus Tan, Rivera & Daguplo, sp. nov. and Scytocera (Scytocera) musa Tan & Rivera, sp. nov. We also describe the calling song of Anthracites sineaureus Tan, Rivera & Daguplo, sp. nov. From different parts of the mountain range, we found and report here the color variation of Anthracites zebra Hebard, 1922.